1994
DOI: 10.1073/pnas.91.11.5158
|View full text |Cite
|
Sign up to set email alerts
|

Cloning, expression, and localization of a chloride-facilitated, cocaine-sensitive serotonin transporter from Drosophila melanogaster.

Abstract: We report here on the isolation and characterization of a serotonin (SHT) transporter from Drosophila melanogaster. A 3.1-kb complementary DNA clone (dSERT) was found to encode a protein of 622 amino acid residues with a predicted molecular mass of w69 kDa and a putative transmembrane topology characteristic of cloned members of the mammalian Na+/Cl-neurotransmitter cotransporter gene family. dSERT displays highest overall amino acid sequence identity with the mammalian 5HT (51%), norepinephrine (47%), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
113
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(118 citation statements)
references
References 43 publications
5
113
0
Order By: Relevance
“…In depressed patients, Bolo et al, 2000, using Magnetic Resonance Spectroscopy of the 19 F signal naturally present in Flx and norfluoxetine (NFlx), found that doses of Flx of 10-40 mg/day for 3-12 months resulted in Flx brain concentrations of 1377 mM, that, using 0.0023 as the unbound fraction (Liu et al, 2005), would give a drug concentration of 39 nM, that is 13 times the K i for Flx in human SERTs (Demchyshyn et al, 1994). Similar results were obtained by Strauss et al (2002).…”
Section: Discussion Low Levels Of Flx and Rbx Induce Specific Changesmentioning
confidence: 99%
“…In depressed patients, Bolo et al, 2000, using Magnetic Resonance Spectroscopy of the 19 F signal naturally present in Flx and norfluoxetine (NFlx), found that doses of Flx of 10-40 mg/day for 3-12 months resulted in Flx brain concentrations of 1377 mM, that, using 0.0023 as the unbound fraction (Liu et al, 2005), would give a drug concentration of 39 nM, that is 13 times the K i for Flx in human SERTs (Demchyshyn et al, 1994). Similar results were obtained by Strauss et al (2002).…”
Section: Discussion Low Levels Of Flx and Rbx Induce Specific Changesmentioning
confidence: 99%
“…Due to their anatomical and physiological characteristics [8,24,37], as well as their accessibility to pharmaco-behavioral manipulations [28,47], monoamine neuromodulatory systems have received particular emphasis in previous research with decapod crustaceans. Furthermore, evidence for conserved, monoamine reuptake mechanisms in invertebrates [15,18,49] suggests the existence of the requisite sites of action (e.g., see ref. [28]) for testing drug-sensitive reward in this group.…”
Section: Introductionmentioning
confidence: 99%
“…The 2.3 kb dSERT BglII fragment was blunt-ended and cloned into the blunt-ended BamHI site of pBluescript KS ϩ plasmid (Stratagene, La Jolla, CA) downstream of the T7 promotor (Demchyshyn et al, 1994). cRNA was transcribed in vitro using the Ambion mMessage mMachine T7 In Vitro Transcription Kit.…”
Section: Methodsmentioning
confidence: 99%
“…In this system, it was also shown that 5 to 12 Na ϩ ions could "escape" into the cell during each transport cycle, thus generating an ionic current in excess of the predicted electroneutrality of coupled transport in mammalian SERTs. Corey et al (1994) and Demchyshyn et al (1994) cloned the Drosophila serotonin transporter (dSERT) and studied its ionic dependence and pharmacological characteristics. In Xenopus oocytes expressing dSERT, Corey et al report that 5HT uptake depends on Na and Cl.…”
Section: Abstract: Serotonin; Transporter; Uptake; Antidepressants; mentioning
confidence: 99%